Toll-like receptor 2 and poly(ADP-ribose) polymerase 1 promote central nervous system neuroinflammation in progressive EAE - Farez, Mauricio F; Quintana, Francisco J; Gandhi, Roopali; Izquierdo, Guillermo; Lucas, Miguel; Weiner, Howard L (Nature immunology, 2009)
The mediators that drive the progressive phase of multiple sclerosis remain undefined. Weiner and colleagues find that 15α-hydroxycholestene is expressed abundantly only during progressive multiple sclerosis and activates macrophages, microglia and astrocytes via poly(ADP-ribose) polymerase 1. Multiple sclerosis is an inflammatory disease of the central nervous system that begins as a relapsing-remitting disease (RRMS) and is followed by a progressive phase (SPMS). The progressive phase causes the greatest disability and has no effective therapy, but the processes that drive SPMS are mostly unknown. Here we found higher serum concentrations of 15α-hydroxicholestene (15-HC) in patients with SPMS and in mice with secondary progressive experimental autoimmune encephalomyelitis (EAE) but not in patients with RRMS. In mice, 15-HC activated microglia, macrophages and astrocytes through a pathway involving Toll-like receptor 2 (TLR2) and poly(ADP-ribose) polymerase 1 (PARP-1). PARP-1 activity was higher in monocytes of patients with SPMS, and PARP-1 inhibition suppressed the progression of EAE. Thus, the TLR2–PARP-1 pathway is a potential new therapeutic target in SPMS.